Customer willingness to participate in value co-creation: The moderating effect of social ties (empirical study of automobile customers in Ghana) - Christian Narh Opata; Wen Xiao; Angela Abena Nusenu; Stephen Tetteh; Emmanuel Sackitey Opata (Cogent Business & Management, 2019)
Value co-creation as a social process involves the interactions and dialogues between stakeholders. As such, the social ties that stakeholders develop have the propensity to influence their level of interaction in a co-creation activity. In this study, we examine the effect of social ties on consumer's level of interaction and looked at how it moderates on consumers' willingness to engage in interaction leading to co-creation. Data was collected from 535 automobile owners in Ghana through a self-administered questionnaire. The data was analyzed using structural equation model in AMOS and statistical tool package. The test results on consumers' willingness and level of interaction, willingness and co-creation, social ties and level of interaction, social ties and co-creation, interaction and co-creation are significant. On the moderating effect of social ties on willingness, the result shows that social ties strengthen the positive relationship between willingness and interaction. We propose that organizations should manage social ties they develop with their customers effectively so as not to impact negatively on their willingness to engage in co-creation interactions.
Keywords: 650; social ties; willingness; interaction; co-creation